The role of a plant-based diet in the pathogenesis, etiology and management of the inflammatory bowel diseases - Grosse, C.S.J.; Christophersen, Claus; Devine, A.; Lawrance, I.C. (TAYLOR & FRANCIS LTD, 2020)
© 2020 Informa UK Limited, trading as Taylor & Francis Group.